Uncivil disobedience : studies in violence and democratic politics - Kirkpatrick, Jennet, 1970- (Princeton University Press, 2008)
"Uncivil Disobedience examines the roles violence and terrorism have played in the exercise of democratic ideals in America. Jennet Kirkpatrick explores how crowds, rallying behind the principle of popular sovereignty and desiring to make law conform to justice, can disdain law and engage in violence. She exposes the hazards of democracy that arise when citizens seek to control government directly, and demonstrates the importance of laws and institutions as limitations on the will of the people." "Kirkpatrick looks at some of the most explosive instances of uncivil disobedience in American history: the contemporary militia movement, Southern lynch mobs, frontier vigilantism, and militant abolitionism. She argues that the groups behind these violent episodes are often motivated by admirable democratic ideas of popular power and autonomy. Kirkpatrick shows how, in this respect, they are not so unlike the much-admired adherents of nonviolent civil disobedience, yet she reveals how those who engage in violent disobedience use these admirable democratic principles as a justification for terrorism and killing. She uses a "bottom-up" analysis of events to explain how this transformation takes place, paying close attention to what members of these groups do and how they think about the relationship between citizens and the law." "Uncivil Disobedience calls for a new vision of liberal democracy where the rule of the people and the rule of law are recognized as fundamental ideals, and where neither is triumphant or transcendent."--Jacket